RESILIENCE LEVEL OF THE STUDENTS’ PARENTS WITH VARIOUS DEVELOPMENTAL DISORDERS - Hakhverdyan, N.; laverdyan, H.; Baghdagyulyan, N. (SUSh Scientific Proceedings, 2025)
Children with various developmental disorders face numerous challenges related both to the specific characteristics of their development and to the difficulties of inclusion in social environments and adaptation to educational processes. These factors often lead to high levels of stress and emotional instability among parents, which, in turn, has negative effects not only on their psychological well-being but also the overall atmosphere within the family. The article aims to identify the level of stress resilience and emotional instability among the students’ parents affected by various developmental disorders. The objectives of the article are to develop and conduct research on the stress resilience and emotional instability levels among the students’ parents with different developmental disorders and to provide recommendations on stress level reduction. The relevance of the topic lies in the fact that this essential issue still requires further study, and our attempt is to reveal the level of stress resilience and emotional instability among such parents; which is crucial in the parenting process. To carry out the research, we have systematized the theoretical literature. Additionally, we have applied observation methods, psychological interviews, the ―Parental Stress Scale‖ (adapted by Yu. V. Misiyuk and I. V. Tikhonova) to assess the general level of parental stress To conduct the research, we used observation, psychological interview, and the ―Parenting Role Satisfaction Methodology‖ (adapted by E. V. Kuftyaki) to evaluate parents' satisfaction with their parental role. Based on the results of the study conducted in the communities of Goris, Verishen, Akner, Hartashen, and Nerkin Khndzoresk in the Syunik Region, we concluded that students’ parents with various developmental disorders experience a high level of stress. This is mainly due to their insufficient awareness of inclusive educational environments and fears for the future.